Visiting Family and Friends in Southern California - Watkins, Howard::::::::: (1978)
Howard Watkins, Adam Watkins sitting on lap of Reverend Stephen Fritchman Minister at 1st Unitarian Church of Los Angeles; married Christine and Howard Watkins